TRANSFORMATION OF STATE POLICY ON INTERNALLY DISPLACED PERSONS IN UKRAINE - Sychova , V.; Kapinus , O. (Pressing Problems of Public Administration, 2020)
The Russian aggression against Ukraine (since 2014) has contributed to further development of civil society. A growing number of the actors of internally displaced persons policy (IDP) and their enhanced impact on political process have changed the nature of the state IDP policy in Ukraine. The research task is substantiation of a gradual transformation of the state policy on internally displaced persons in Ukraine towards public policy, that is, a growing impact of civil society institutions on the processes of the IDP policy-making and implementation in Ukraine, as well as expansion of the variety of public policy tools for the interaction of political process actors. The authors prove that the activity of the new public policy actors (in particular, the Citizens’ initiative “CrymSOS”, charitable foundations “Vostok-SOS” and “The Right to Protection”, NGO “Civil Holding Group of Influence”) gave rise to introducing the issues of protection of the rights and freedoms, and strengthening of the employment capacity of forced migrants into the state policy domain. The country’s leadership has realized the importance of establishing and strengthening partnership with civil society. There have been further structural and functional transformations of public institutions that were losing their traditional character and experiencing innovations. From February 2016, public authorities and civil society institutions have implemented public policy tools regarding IDP: interaction between the authorities and public associations representatives (The Coordination Council for the Promotion of Civil Society Development under the President of Ukraine, the Public Council of the Ministry for Temporarily Occupied Territories and Internally Displaced Persons of Ukraine); parliamentary hearings, petitions, public expertise, expert and analytical structures, public monitoring of the authorities, public budget. However, since September 2019, under the lack of comprehensive coordinated activities on behalf of the state as to the making and implementing of IDP policies, the initiative in protection of the rights and freedoms of internally displaced persons has been taken by civil society institutions. It can be asserted that the state IDP policy has acquired all the features of a public policy. The authors designate three periods in the process of the transformation of the state IDP policy: 1) October 2014 – February 2016 – the state IDP policy started transformation towards public policy; 2) February 2016–August 2019 – institutionalization of public IDP policy took place; 3) September 2019–to present – further development of the public IDP policy continues in connection with the increased significance of civil society institutions.